Dinamika Psikologis Pasangan yang Bercerai di Masa Pandemi Covid 19 (Studi Kasus Pada Warga Desa Tipar Kecamatan Rawalo Kabupaten Banyumas) - Faishol, Lutfi; Aryani, Lilis Dwi (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah IAI Miftahul Ulum Pamekasan, 2022)
Psychological dynamics is the relationship between various psychological aspects that exist in the respondent in relation to the condition of society. The psychological community will certainly be disturbed after the emergence of the COVID-19 pandemic, especially for married couples who are divorced during the pandemic. This study aims to determine how the psychological dynamics of divorced couples during the COVID-19 pandemic. This study uses a qualitative method with a case study approach. Data was collected by means of interviews, observation and documentation. In general, the factors causing divorce during the COVID-19 pandemic occurred due to conflicts in the household caused by economic problems, domestic violence, disputes, and emotional factors. Based on the results of the study, it can be concluded that the psychological dynamics of married couples who divorced during the COVID-19 pandemic in this study were worries/traumatic feelings, emotional disturbances, depression, stress, and also experienced feelings of guilt. This is experienced by subjects with different levels. The subjects in this study were 2 married couples who divorced during the COVID-19 pandemic who lived in Tipar Village, Banyumas District. With this research, it is expected to be able to make understanding for the community and try to minimize the divorce rate and if possible, the role of social workers must be included to help handle divorce and help create new programs as a form of preventive effort for people who are married to avoid divorce when pandemic period. Keywords: Divorce, The COVID-19 Pandemic, Psychological Dynamics